Gossypol glands in relation to resistance to bollworm (Helicoverpa armigera) in upland cotton (Gossypium hirsutum) - RAJARAJESWARI, V; SUBBARAO, I V (The Indian Journal of Agricultural Sciences, 2013)
Correlation of gossypol glands on plant surface of upland cotton (Gossypium hirsutum L.) and incidence of bollworm(Helicoverpa armigera Hubner) was studied at Lam in 1992-93 and 1993-94. Distribution of gossypol glands was foundhigh on ovary surface compared with that on leaf, calyx and bract of upland cotton. The genotypes 'ORs 75-75','JK260-2', 'Glabrous Line', 'RFS 3438', 'Tx Lamo 21-5-1-18', 'NA 1325' and 'Tx Maroon 2-78' with more number of gossypol glands on these plant parts recorded low incidence of bollworm, whereas those with fewer gossypol glands showed moderate to high incidence. Association of gossypol glands on leaf and ovary surface showed significantlyÂ negative association with bollworm incidence. Association among gossypol glands on different surfaces of plant was positive and significant.